1989
DOI: 10.3171/jns.1989.70.6.0862
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for lower respiratory tract infections after brain-tumor surgery

Abstract: Nosocomial infection of the lower respiratory tract is a frequent and serious complication after major operations. A 32% incidence of lower respiratory tract infections was found after brain-tumor surgery in 289 patients, with a 21% incidence of pneumonia. In 186 of these patients (Group A), five factors were identified which were associated with an increased risk of postoperative lower respiratory tract infection. These were: age, tumor type, cardiac insufficiency, preoperative disturbances of consciousness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…5,13,19,20,23 Old age itself has been identified as an indicator of a poor prognosis. 6,11,17,22 Studies have also documented high postoperative mortality and morbidity rates in elderly patients with meningiomas and schwannomas, 1,2,21 but in light of the beneficial effects obtained with benign tumor resection, many authors recommend proceeding with surgery in such patients. 14,26,30 Tomita and Raimondi 35 studied 80 elderly patients with brain tumors, including benign tumors, and reported that a total of 27 postoperative systemic complications developed in 23 patients.…”
Section: Discussionmentioning
confidence: 99%
“…5,13,19,20,23 Old age itself has been identified as an indicator of a poor prognosis. 6,11,17,22 Studies have also documented high postoperative mortality and morbidity rates in elderly patients with meningiomas and schwannomas, 1,2,21 but in light of the beneficial effects obtained with benign tumor resection, many authors recommend proceeding with surgery in such patients. 14,26,30 Tomita and Raimondi 35 studied 80 elderly patients with brain tumors, including benign tumors, and reported that a total of 27 postoperative systemic complications developed in 23 patients.…”
Section: Discussionmentioning
confidence: 99%